Serious Games for Training Myoelectric Prostheses through Multi-Contact Devices - Rosa M. Carro; Fernando G. Costales; Alvaro Ortigosa (MDPI AG, 2022)
In the medical context, designing and developing myoelectric prostheses has made it possible for patients to regain mobility lost due to amputations; however, their use requires intensive training. Serious games through multi-touch devices can serve as a complement to the activities carried out during face-to-face sessions with occupational therapists and physiotherapists, as a useful resource to engage patients, especially children, and make them enjoy training. In this paper, we describe our work to support the training of myoelectric prostheses through digital serious games. Firstly, we studied the needs of children with myoelectric prostheses and the way they perform rehabilitation. Secondly, we designed specific games to support training accordingly. Thirdly, we developed a system able to generate variations of these games dynamically, adapting the elements at each round to the needs and progress of each child. The interfaces are simple, friendly, and based on tablets to favor autonomy. Finally, we assessed the potential of the use of these games for rehabilitation. Specialists in Physiotherapy, Occupational Therapy, Medicine and Special Education collaborated as experts; they agreed that SilverTouch is good for myoelectric prosthetic training and confirmed its potential to be widely used in this context.